LOOPER: a molecular mechanics-based algorithm for protein loop prediction - Spassov, Velin Z.; Flook, Paul K.; Yan, Lisa (Protein engineering, design and selection, 2008)
We describe a new ab initio method and corresponding program, LOOPER, for the prediction of protein loop conformations. The method is based on a multi-step algorithm (developed as a set of CHARMm scripts) and uses standard CHARMm force field parameters for energy minimization and scoring. One of the main obstacles to ab initio computational loop modeling is the exponential growth of the backbone conformational states with the number of residues in the loop fragment. In contrast to many ab initio algorithms that use Monte-Carlo schemes or exhaustive sampling, LOOPER adopts a systematic search strategy with minimal sampling of the backbone torsion angles. During the initial conformational sampling, two representative states are sampled for each alanine-like residue based on pairs of initial φ and ψ dihedral angles, except glycine, which is sampled by four representative conformations. The initial (φ, ψ) values are determined from the analysis of a novel iso-energy contour map which is proposed as an alternative structure validation method to the widely used Ramachandra plot. The efficient sampling strategy is combined with energy minimization at each step. The initial energy minimization and scoring of the loop include the interactions of the protein core with loop backbone atoms only. Construction and optimization of the side-chain conformations is followed by a final ranking stage based on the CHARMm energy with a generalized Born solvation term as a scoring function. The systematic and efficient sampling strategy in LOOPER consistently finds near native loop conformations in our validation study. At the same time, the computational overhead of our method is significantly lower than many alternative approaches that use exhaustive search strategies.